2010
DOI: 10.1128/mcb.01450-08
|View full text |Cite
|
Sign up to set email alerts
|

The RasGAP Proteins Ira2 and Neurofibromin Are Negatively Regulated by Gpb1 in Yeast and ETEA in Humans

Abstract: The neurofibromatosis type 1 (NF1) gene encodes the GTPase-activating protein (GAP) neurofibromin, which negatively regulates Ras activity. The yeast Saccharomyces cerevisiae has two neurofibromin homologs, Ira1 and Ira2. To understand how these proteins are regulated, we utilized an unbiased proteomics approach to identify Ira2 and neurofibromin binding partners. We demonstrate that the Gpb1/Krh2 protein binds and negatively regulates Ira2 by promoting its ubiquitin-dependent proteolysis. We extended our find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 46 publications
2
57
0
Order By: Relevance
“…76 Recently, Phan et al identified the ETEA/UBXD8 protein to interact and promote NF1 ubiquitination and degradation, which would ultimately regulate the amount of NF1 at the cell surface. 77 It is unknown if these findings are linked to earlier studies reporting that NF1 phosphorylation inhibits its lysosomal degradation. 78 Interestingly, ETEA/UBXD8 does not interact with p120GAP, 77 the other ubiquitously expressed RasGAP, indicative of this interaction contributing to differential and spatiotemporal Ras signaling.…”
Section: Nf1mentioning
confidence: 70%
See 1 more Smart Citation
“…76 Recently, Phan et al identified the ETEA/UBXD8 protein to interact and promote NF1 ubiquitination and degradation, which would ultimately regulate the amount of NF1 at the cell surface. 77 It is unknown if these findings are linked to earlier studies reporting that NF1 phosphorylation inhibits its lysosomal degradation. 78 Interestingly, ETEA/UBXD8 does not interact with p120GAP, 77 the other ubiquitously expressed RasGAP, indicative of this interaction contributing to differential and spatiotemporal Ras signaling.…”
Section: Nf1mentioning
confidence: 70%
“…77 It is unknown if these findings are linked to earlier studies reporting that NF1 phosphorylation inhibits its lysosomal degradation. 78 Interestingly, ETEA/UBXD8 does not interact with p120GAP, 77 the other ubiquitously expressed RasGAP, indicative of this interaction contributing to differential and spatiotemporal Ras signaling.…”
Section: Nf1mentioning
confidence: 70%
“…While numerous binding partners of neurofibromin have been reported (Patrakitkomjorn, et al, 2008;Phan, et al, 2010;Welti, et al, 2008), the physiological significance of the underlying protein-protein Welti, et al, 2007). A number of missense mutations of the Sec14-PH module have been identified in NF1-patients as well as single and double amino acid deletions (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wang and colleagues found that neither IBMPFD-associated mutant VCP nor dominant negative VCP affected NF1 stability or ubiquitination state. This is surprising, because others have found that NF1 protein levels can be stabilized by genetic knockdown of another known VCP cofactor and NF1 interactor, UBXD8 (18). Whether UBXD8 is the missing link between VCP and NF1 in mediating synaptogenesis remains to be studied.…”
Section: Vcp Interacts With Nf1 In the Brain And Mediates Synaptogenesismentioning
confidence: 79%
“…Sudhof and Sugita have previously immunoprecipitated the synaptic vesicle protein synaptotagmin 1 (Syt1) from rat brain and identified VCP as an interactor (19). VCP associates with Syt1 in a Ca 2+ -dependent manner; however, unlike most specialized synaptic proteins, VCP is expressed at high levels in all tissues examined and did not increase during postnatal brain development, when synaptogenesis occurs (18). VCP has also been found to associate with another presynaptic protein, strumpellin, which is mutated in a dominant form of familial spastic paraplegia (SPG8) (20,21).…”
Section: Vcp Interacts With Nf1 In the Brain And Mediates Synaptogenesismentioning
confidence: 99%